Partially coherent seeding of supercontinuum generation in picosecond regime. (December 2019) - Jiang, Ziqi; Wang, Tianshu; Sun, Zhiwen; Chen, Junda; Zhang, Xinmeng; Lin, Peng; Chen, Peidi; Zhao, Yiwu
Highlights: Experimental demonstration of partially coherent seeding in supercontinuum generation. Detailed descriptions of optical rogue events. Statistical analysis on pulse-to-pulse fluctuation of supercontinuum. Coherence properties of partially coherent seeded supercontinuum. Abstract: The practicability of picosecond supercontinuum (SC) is greatly limited by the noise-seeded modulation instability (MI) in SC generation. In this letter, we experimentally demonstrate SC generation in picosecond regime with control of MI process. With partially coherent seeding involved in SC generation, the pulse-to-pulse fluctuation is greatly improved while the coherence of SC valued by interference fringes keep at a low level that similar with non-seeding SC. Taking these features into account, we believe that the SC with partially coherent seeding can be a suitable source for applications requiring high pulse stability with low coherence such as free space optical (FSO) communication and optical coherence tomography (OCT).